Swipe up for more! ebook Inside the unfiltered lives of influencers. - McNeal, Stephanie (2023)
An unfiltered, colorful romp through the IRL world of influencers that spills the tea on the multibillion-dollar industry of content creation. If you’re anything like journalist Stephanie McNeal—aka, a millennial woman—you spend hours every day indulging in Instagram’s infinite scroll. The influencers on the platform aren’t just providing eye candy; these tastemakers impact how we cook, consume, parent, decorate, think, and live. But what exactly is going on behind the curtain of the perfectly curated Instagram grids we obsess over the most?  Through intimate, funny, and vulnerable reporting, McNeal takes us through the looking glass and into the secretive real world of three major influencers: fashion and lifestyle juggernaut Caitlin Covington of Southern Curls & Pearls, runner and advocate Mirna Valerio, and OG “mommy blogger” Shannon Bird. Swipe Up For More! is based on three years of unprecedented, fly-on-the-wall access that offers a rare glimpse into how these influencers build their empires, struggle with the haters and snarkers, fight for creative control from the tech platforms that enable their businesses, parent in public, and try to look good while doing it. Along the way, McNeal answers burning questions, like: Why are there so many Mormon mommy influencers? What is it like to work for a popular influencer? What do they do with all the free swag? How do brand partnerships work? And how much money do they really make? Irresistible, juicy, and voyeuristic, Swipe Up For More! reveals all about the women some love to hate (and many actually, secretly, genuinely love).